Designing A Neural Network Model in Grading Malaysian Rice - Che Pa, Noraziah; Yusoff, Nooraini; Ahmad, Norhayati (International Journal of Engineering and Technology, 2018)
Un-consistency of rice evaluating rehearses in Malaysia came about numerous methodologies utilized by zones which effectively creating rice in Malaysia. Understanding the significance of rice reviewing process in guaranteeing rice quality can be controlled, it is critical to have a standard rice evaluating approach for the referenced reason. To accomplish this, there are two essential viewpoints that should be considered in structuring rice reviewing model; evaluating system and variables to be utilized for evaluating (generally alluded as rice characteristics). This article proposes a Neural Network (NN) demonstrate for evaluating Malaysian rice. To apply the model, twenty one rice highlights are proposed to be utilized. Mix of broad writing survey and arrangement of meeting were utilized in deciding the highlights. To assess the model, master survey was led including area specialists and skill of NN. The proposed model is accepted to be gainful for BERNAS as well as to different specialists in a similar space.. The NN model can be utilized as direction or reference for comparative reviewing works.Â Â